Peran Guru dalam Pengembangan Kurikulum Merdeka - Saputro, Fathan Faris; Zainal Arifin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Findings from various sources are gathered in this article to highlight the important role of educators in developing curriculum. Teachers must successfully implement the curriculum in the classroom as part of their function as educators. They play an important role in the teaching process. Meanwhile, the curriculum functions as a framework for organizing and planning educational resources used in teaching and learning activities. The background to writing this article arises from the author's understanding of indications that the role of teachers is not optimal, especially in applying the concept of an independent curriculum. The purpose of this article is to dig deeper into the role of teachers in developing an independent curriculum. The research method used is library research or library research, involving various sources such as books, articles and related research. The authors' findings highlight how important it is for teachers to play a critical role in developing curriculum in educational institutions, focusing on their capacity to communicate knowledge effectively so that the curriculum can be implemented. The analysis and conclusions of the discussion chapter produce useful recommendations, such as how important it is for educators to understand technological advances, how to adapt to an ever-changing curriculum, and how to prioritize tasks so they can be completed efficiently.